Youth and mental health problems in Malaysia - Hamzah, Siti Raba'ah; Musa, Siti Nur Syuhada; Mohamed, Nor Hidayah; Osman, Saripah; Yahya, Shahhanim (Human Resources Management Academic Research Society (HRMARS), 2023)
This study aims to identify the level of mental health issues among Malaysian youth and ascertain the extent to which they are affected by depression, anxiety, and stress. This study also seeks to determine the extent to which these issues are associated with suicidal intentions. The data were obtained from the Youth Development Index (YDI) with two cohorts which comprised 8,332 respondents in 2019 and 21,126 respondents in 2020. The respondents completed a self-administered questionnaire, DASS-21, which used a depression scale, an anxiety scale, a stress scale, and a scale for suicide ideation (SSI-C) that indicates the intention to commit suicide. The results showed that, unlike depression and anxiety, there was a considerable increase in the percentage of youth with medium and high levels of stress and suicide attempts in 2020 compared to 2019. The findings provide a better understanding of youth with mental health problems in Malaysia.